HUBUNGAN KEAKURATAN KODE DIAGNOSIS DAN TINDAKAN DENGAN BESARAN TARIF INA-CBGS KASUS DIABETES MELITUS TIPE II DI RSUD ANUTAPURA PALU - Yusnaeni, Yusnaeni; Muchlis, Husni Abdul; Hosizah, Hosizah; Qomarania, Witri Uama (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: The accuracy of the diagnosis and action codes is related to the amount of INA-CBG costs that will be claimed. Initial observation results showed that of the 31 claim files there were 17 (54.8%) with inaccurate codes. This study aims to determine the relationship between the accuracy of diagnosis codes and actions with the INA-CBGs rates for type II DM cases at Anutapura Regional Hospital, Palu, in January – August. This type of research is quantitative research with a cross sectional research design. The population size was 387 and the sample size was 79 claim files using a simple random sampling technique. Data collection was carried out through document review of inpatient claim files and INA-CBGs rates. Data analysis using the Chi-Square test. The research results from 79 claim files contained 25 (31.6%) inaccurate diagnosis with inaccurate INA-CBGs rates. The results of the Chi-Square test by looking at the Fisher's exact test value show that there is a relationship between the accuracy of the diagnosis code and the action and the INA CBG's rates for type II DM cases at Anutapura Regional Hospital with a p-value of 0.04 < 0.05 and an OR value = 3.811 This means that the accuracy of the diagnosis and action codes has a 3.811 chance of producing the correct INA-CBGS rate. It is hoped that coders will be more careful in assigning accurate codes according to ICD-10 and ICD-9 rules in order to produce the correct INA-CBGs rates. Keyword: Accuracy Of Diagnosis and Action Codes, ICD-10 and ICD-9 Coding, INA-CBGs Rates Abstrak: Keakuratan kode diagnosis dan tindakan berhubungan dengan besaran tarif biaya INA-CBGs yang akan diklaim. Hasil observasi awal menunjukkan dari 31 berkas klaim terdapat 17 (54.8%) dengan kode yang tidak akurat. Penelitian ini bertujuan untuk mengetahui hubungan keakuratan kode dengan besaran tarif INA-CBGs kasus DM tipe II di RSUD Anutapura Palu pada bulan Januari – Agustus. Jenis penelitian ini adalah penelitian kuantitatif dengan rancangan cross sectional. Besar populasi sebanyak 387 dan besar sampel sebanyak 79 berkas klaim dengan teknik simple random sampling. Pengumpulan data dilakukan melalui telaah dokumen terhadap berkas klaim rawat inap dan besaran tarif INA-CBGs. Analisis data dengan uji Chi-Square. Hasil penelitian dari 79 berkas klaim terdapat 25 (31.6%) kode diagnosis dan tindakan yang tidak akurat dengan tarif INA-CBGs yang tidak tepat. Hasil uji Chi-Square dengan melihat nilai fisher’s exact test menunjukkan ada hubungan antara keakuratan kode diagnosis dan tindakan dengan besaran tarif INA CBG’s kasus DM tipe II di RSUD Anutapura dengan nilai p-value sebesar 0,04 < 0,05 dan nilai OR=3,811 artinya keakuratan kode diagnosis dan tindakan mempunyai peluang 3,811 kali menghasilkan tarif INA-CBGS yang tepat. Diharapkan petugas koder lebih teliti dalam menetapkan kode yang akurat sesuai aturan ICD-10 dan ICD-9 agar dapat menghasilkan tarif INA-CBGs yang tepat. Kata kunci: Keakuratan Kode Diagnosis dan Tindakan, Pengkodean ICD-10 dan ICD-9, Tarif INA-CBGs